Stock Splits Mampukah Memprediksi Perubahan Laba Masa Datang - Yusni Warastuti; Widuri Kurniasari (Jurnal Ilmiah Aset, 2008)
This study examines whether stock splits announcement contain information about future profitability, measured in terms of future earnings change. Our empirical result show evidence that runup price and price prior stock splits event are positively related to stock split factor and significant. Indeed, we find that split factors signal not only unable to predict future earnings change, after controlling for current profitability.